(In)credibly queer? Assessments of asylum claims based on sexual orientation - Selim, Hedayat; Lindblad, Pia; Vanto, Johanna; Skrifvars, Jenny; Alvesalo‐Kuusi, Anne; Korkman, Julia; Pirjatanniemi, Elina; Antfolk, Jan (Wiley, 2025)
Purpose: Queer asylum-seekers should be given an oppor-tunity to have their claim evaluated in a fair and unbiasedmanner. Despite this, research shows they risk having theirclaims rejected based on stereotypes about sexual minori-ties. In the present study, we investigated how the FinnishImmigration Service evaluated credibility in asylum claimslodged by sexual minorities.
Methods: We analysed 68 negative asylum decisions to as-sess the arguments made to reject the asylum claim. To dothis, we developed a detailed coding scheme to investigatethe specific themes and credibility indicators cited in theasylum decisions.
Results: We found that the asylum claims were most oftenrejected because the applicant's account of their sexual ori-entation was not found to be sufficiently detailed, consist-ent, or plausible. Officials appeared to hold assumptionsaround sexual identity development and interpersonal rela-tionships that are partially unsupported by established psy-chological science.
Conclusions: Assessments of SOGI claims would benefitfrom a greater consideration of the factors affecting queerasylum applicants' ability to describe their claims, includingcross-cultural differences in understandings of sexuality,variability in human behaviour, and practical barriers withinthe asylum procedure.